Gold prices fluctuation of co-movement forecast between China and Russia. (August 2019) - Zhong, Wanxing; Kong, Rui; Chen, Guang
Abstract: In the past two years, China's gold development and investment in Russia has become a trend, the paper is conducted to provide the price reference for gold investors. This paper based on coarse-graining and complex network theory to build the fluctuation of gold prices' co-movement network structure by using the average prices of gold. Then analyzed the network patterns of critical co-movement modes, group, conversion and transition of the co-movement modes. The results show that the complex network is formed by one small group with 11 core modes and two large groups with the core modes of weak positive co-movement (yyyy) and weak negative co-movement (nnnn). The conversion between modes of different large groups requires an average of 6 days. Using weights of the nodes as probability to predict 185 days prices' co-movement from September 2017 to September 2018. The results may provide preferences for investors to avoid risks. Highlights: This paper analyzed the gold prices' co-movement network structure by using the Chinese and Russian gold prices. This paper analyzed the network patterns of critical co-movement modes, group, conversion and transition of the co-movement modes. This research based on coarse- graining and complex network theory.